MODEL 70-20-10 VS ADDIE: A COMPARATIVE ANALYSIS OF LEARNING MODELS FOR ENHANCING APPARATUS COMPETENCE - Manyo'e, Endi Triyanto (Jurnal Administrasi Negara, 2025)
Enhancing apparatus competence is an urgent and crucial matter to address the challenges of modern bureaucracy, which demands rapid adaptation in the digital era. This research aims to comparatively analyze the 70-20-10 and ADDIE learning models for enhancing apparatus competence. The research employs a qualitative approach using the Systematic Literature Review (SLR) method, based on PRISMA. The research results indicate that the 70-20-10 Model, which emphasizes a learning proportion based on experience (70%), social interaction (20%), and formal training (10%), is considered flexible and effective in informal learning and leadership development. However, it’s difficult to be measured and evaluated. Meanwhile, the ADDIE Model, with its systematic stages (Analysis, Design, Development, Implementation, Evaluation), is considered superior in structure and measurability. However, it's less flexible and requires substantial resources. Integrating both models into a hybrid learning approach, which combines the strengths of each, can offer a transformative solution for enhancing apparatus competence and create a holistic approach. The ADDIE model is used to design formal learning that is measurable and systematic, supported by thorough planning, competent facilitators/mentors, digital infrastructure, and a comprehensive evaluation system. Meanwhile, the 70-20-10 model, with its flexibility, will enrich contextual learning through experience and collaboration. The integration of these models will create an inclusive training design through the development of adaptive, efficient, and sustainable apparatus competence, thereby improving the quality of public services.